A single machine EPQ inventory model for a multi-product imperfect production system with rework process and auction. Issue 3 (4th November 2016) - Nobil, Amir Hossein; Taleizadeh, Ata Allah
Abstract : In this paper, a multi-product Economic Production Quantity (EPQ) inventory model for a defective production system by a single machine is considered. The faulty produced products are reworked or are put on auction as they are. The aim of this research is to determine the optimal cycle length and the percentage of reworking every fault product such that the total inventory cost, including setup, production, holding, reworking, and lost profit, is minimized. We have proved that this problem is a convex non-linear programming method. Therefore, we came up with the exact algorithm based on differentiation to solve it. Finally, a sensitivity analysis is performed to evaluate the effect of changes in different parameters of the problem.